Applied statistics in business and economics (Student CD-ROM to accompany) - Doane, David P. (McGraw-Hill/Irwin, 2007)
This new text offers an Excel focused approach to using statistics in business. All statistical concepts are illustrated with applied examples immediately upon introduction. Modern computing tools and applications are introduced, and the text maintains a strong focus on presenting statistical concepts as applied in business --as opposed to providing programming methods used to find a mathematical solution. Interpretation is heavily emphasized, enabling students to take full advantage of Excel to develop and drive problem-solving skills